Antibacterial activity of PEO nanofibers incorporating polysaccharide from dandelion and its derivative. (15th October 2018) - Lin, Lin; Zhu, Yulin; Li, Changzhu; Liu, Lei; Surendhiran, Duraiarasan; Cui, Haiying
Highlights: Polysaccharide from dandelion (PD) was successfully carboxymethylated (CPD). PD/PEO and CPD/PEO nanofibers were fabricated by electrospinning technique. PD/PEO and CPD/PEO nanofibers showed inhibitory effect against L. monocytogenes . Abstract: A water-soluble antibacterial polysaccharide from dandelions (PD) was chemically modified to obtain its carboxymethylated derivative (CPD). The degree of substitution of CPD was 0.455. Fourier transform infrared (FTIR) spectra analysis, zeta potential, particle size and rheological test verified the carboxymethylation of PD, accompanying with the change of physicochemical properties. Moreover, Listeria monocytogenes treated with 10 mg/mL PD and CPD achieved 1.96 and 3.29 log CFU/mL reduction in population, respectively. Subsequently, PD and CPD were incorporated into polyethylene oxide (PEO) nanofiber matrix to fabricate antimicrobial nanofibers. The prepared nanofibers were characterized by scanning electron microscope, atomic force microscope and FTIR. Finally, both PD/PEO and CPD/PEO nanofibers exhibited favourable antibacterial effect on L. monocytogenes, with an improved antibacterial activity of CPD/PEO nanofibers than PD/PEO nanofibers. In conclusion, this study demonstrated PD and CPD could be applied to the fabrication of antibacterial food packaging.